Burden of hemodialysis on health-related quality of life: insights from a multi-center cross-sectional analysis in Southern Albania - Lalo, Rezarta; Kamberi, Fatjona; Stasa, Eda; Lalo, Kenedia (Frontiers in Medicine, 2025)
BackgroundChronic renal failure represents an escalating public health issue globally, including in Albania, due to its substantial impact on morbidity and mortality rates. Since it requires ongoing treatments, such as hemodialysis, the quality of life (QOL) of affected individuals is often severely compromised. Consequently, this study was conducted to assess the burden of hemodialysis on health-related quality of life (HRQOL) and identify the associated factors.MethodsThis is a multicenter, cross-sectional study conducted across three dialysis units through a public-private hemodialysis partnership, covering three major regions of Southern Albania. The Kidney Disease Quality of Life Questionnaire – Short Form (KDQOL-SF) was used for data collection. The data were processed using the statistical software IBM SPSS Statistics for Windows, Version 23.0. Binary logistic regression was used to assess patients’ quality of life in relation to various sociodemographic and clinical factors. A p-value ≤0.05 was considered statistically significant.ResultsThe mean age of participants was 56.1 ± 12.37 years. 97% of patients undergoing hemodialysis had hypertension as a comorbidity and 99% were anemic. The mean scores for the physical and mental component summaries were 34.17 ± 12.99 and 47.52 ± 13.95, respectively. Regarding the overall quality of life score, our findings revealed that females (39.6 ± 8.7), older individuals (42.2 ± 10.4), married patients (44.8 ± 9.9), and those with three or more comorbidities (42.5 ± 9.0) had the lowest scores, indicating the worst quality of life.ConclusionThe data suggest that, age, gender, civil status and number of co-morbidities are significant factors influencing the overall quality of life of hemodialysis patients. Participants with multiple comorbidities, particularly older, female, married, reported the lowest quality of life scores. These findings indicate that such factors may contribute to poorer health outcomes, suggesting the need for tailored interventions by healthcare professionals to reduce the burden of hemodialysis on health-related quality of life.